Spatial Distribution of Some Alkali and Alkaline Earth Metals of Selected Locations in Sulaimani Governorate, Kurdistan Region, Iraq. - Majid, Salih N.; Sheikh-Abdullah, Shuela M. (Sulaimani Journal for Pure and Applied Sciences, 2017)
This study aimed to determine the background concentration and also to assess the distribution pattern of some alkali metals (Na and K) and alkaline earth metals of (Mg, Ca, Be, Sr and Ba) along depth increments (0 to 15 and 15 to 30 cm) of soils from ten (10) locations in Sulaimani Governorate- KRI. The soil samples were digested by aqua regia and then analyzed by inductively coupled plasma-atomic emission spectroscopy (ICP-AES). The results were statistically analyzed through both principal component analysis (PCA) and cluster analysis to show the similarity and dissimilarity of the soils among the studied locations. The results showed that there was no consistent distribution pattern for the studied metal along the selected depths due to the variation of the input sources of the metals and their quantities in the parent materials and/ or to continuous mixing by agricultural operations. It was also found that the contents of the studied metals based on the highest concentration, followed the following sequence Ca > Mg > K > Ba >Sr > Na > Be. According to the results of PCA analysis, the explained variation for two factors accounted for % 60.25 of the total variance. On the other hand, the agglomerative hierarchical clustering classified the soils of the ten locations into four major groups at a significant dissimilarity percent of about 57%.
Keywords: Agglomerative Hierarchical Clustering AHC; Alkaline earth metals; Alkali metal; principal component analysis PCA Sulaimani Governorate